(untitled) - Burd, Barry A. (Hoboken, New Jersey, 2017)
Develop the next killer Android App using Java programming! Android is everywhere! It runs more than half the smartphones in the U.S. and Java makes it go. If you want to cash in on its popularity by learning to build Android apps with Java, all the easy-to-follow guidance you need to get started is at your fingertips. Inside, you'll learn the basics of Java and grasp how it works with Android; then, you'll go on to create your first real, working application. How cool is that? The demand for Android apps isn't showing any signs of slowing, but if you're a mobile developer who wants to get in on the action, it's vital that you get the necessary Java background to be a success. With the help of Java Programming for Android Developers For Dummies, you'll quickly and painlessly discover the ins and outs of using Java to create groundbreaking Android apps no prior knowledge or experience required!
Keywords: Java (Ngôn ngữ chương trình máy tính),Java (Computer program language)